MnO2-Au composite nanomaterial, preparation method and application thereof, and hydrogel composite material
By modifying the MnO2-Au composite nanomaterial formed by spherical gold nanoparticles on the surface of manganese dioxide, combined with polyethylene glycol hydrogel, the problem of poor oxygen radical scavenging effect in the prior art was solved, and significantly promoted diabetic patients Wound healing, achieving efficient oxygen radical scavenging and collagen recovery.
Patent Information
- Application Number
- CN202411317455.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-13
AI Technical Summary
Existing nanomaterials are difficult to effectively remove oxygen free radicals in cells, making it difficult for diabetic patients to heal wounds. The existing technology has average results and is difficult to meet actual needs.
Develop a MnO2-Au composite nanomaterial to modify spherical gold nanoparticles on the nanoflower-like manganese dioxide surface, and use the surface plasmon resonance effect of Au to construct an efficient oxygen radical scavenger material and combine it with polyethylene dichloride. Alcohol hydrogels combine to form hydrogel composites.
MnO2-Au composite nanomaterials significantly improve the ability of oxygen free radical removal, promote wound healing, reduce oxidative stress damage in cells, restore collagen expression, significantly improve wound healing efficiency, and hydrogel composites can continue Release of MnO2-Au composite nanomaterials extends the oxygen radical scavenging effect.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a MnO2-Au composite nano material, a preparation method and application thereof, and a hydrogel composite material. Background Art
[0002] Diabetes is a group of disorders of carbohydrate, protein and fat metabolism caused by absolute or relative insulin deficiency and / or insulin utilization disorder. It is characterized by high blood sugar and is one of the major chronic diseases that affect human health. Among them, diabetic foot is one of the common complications of diabetes and one of the main causes of non-traumatic amputation. Its pathogenic mechanism is related to the long-term non-healing of wound ulcers caused by diabetes, which seriously affects the quality of life of patients.
[0003] Oxidative stress is an important factor in the imbalance of the intracellular environment. In the human body, cellular reactive oxygen species (ROS), also known as oxygen free radicals, are an important free radical that can cause oxidative stress reactions and have adverse effects on cells. Oxidative stress is an important reason why diabetic wounds are difficult to heal. Under high-sugar microenvironment conditions, cells promote the occurrence of chronic inflammation by generating excessive reactive oxygen species, and the release of inflammatory factors further promotes the generation of reactive oxygen species. The abnormal function of epithelial cells and decreased cell activity caused by excessive accumulation of reactive oxygen species will slow down the wound healing process. Long-term high sugar and chronic inflammatory states also have a certain impact on wound closure. It is worth noting that the number of antioxidant-related enzymes in the body has not increased significantly with the concentration of reactive oxygen species, which further verifies the necessity of intervention when oxidative stress damage occurs in the early stages of diabetic damage.
[0004] At present, nanoscale materials for inhibiting oxidative stress include MnO2 nanomaterials, CeO2 nanomaterials, Au nanoparticles, C3N4 nanofusiform materials, etc. However, their effects are general and difficult to meet the actual needs of diabetic patients. Therefore, it is of great significance to study and develop a new type of material for scavenging intracellular oxygen free radicals to inhibit oxidative stress and promote wound healing. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a MnO2-Au composite nanomaterial and its preparation method and application, and a hydrogel composite material. The MnO2-Au composite nanomaterial has excellent continuous oxygen free radical scavenging ability, and the hydrogel composite material prepared by the MnO2-Au composite nanomaterial has a more excellent oxygen free radical scavenging function, which can significantly promote the healing of wounds.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a MnO2-Au composite nano material, which is composed of nano-flower-shaped manganese dioxide and spherical gold nanoparticles loaded on the surface of the manganese dioxide.
[0008] Preferably, the Au loading in the MnO2-Au composite nanomaterial is 0.8 wt%~1.2 wt%; more preferably, 1.0 wt%~1.2 wt%; further preferably, 1.18 wt%.
[0009] Preferably, the particle size of the spherical gold nanoparticles is 18-28 nm; more preferably 22.81 nm.
[0010] The spherical gold nanoparticles are uniformly dispersed on the surface of the nanoflower-shaped manganese dioxide.
[0011] Preferably, the particle size of the MnO2-Au composite nanomaterial is 470-630 nm; more preferably 500-600 nm; in some specific embodiments of the present invention, preferably 540 nm.
[0012] The MnO2-Au composite nanomaterial achieves efficient oxygen free radical scavenging by modifying Au nanoparticles on the surface of the metal oxide MnO2. Based on the surface plasmon resonance effect (SPR effect) of Au, an Au-modified MnO2 material, i.e., a MnO2-Au composite nanomaterial, is constructed that can sustainably scavenge active oxygen (oxygen free radicals) at the nanoscale.
[0013] The MnO2-Au composite nanomaterial of the present invention has a weaker degree of oxidative stress damage to HDF cells (human dermal fibroblasts) than MnO2 nanomaterials, indicating that the degree of wound healing damage is weaker and the wound is easier to heal. In addition, the MnO2-Au composite nanomaterial of the present invention can make the ROS level in HDF cells extremely low, indicating that it has a strong ability to scavenge oxygen free radicals. In addition, the MnO2-Au composite nanomaterial of the present invention can more effectively restore the expression of the COL-1A1 gene (encoding collagen type I α chain, the most abundant collagen in the human body) in HDF cells under oxidative stress stimulation than MnO2 nanomaterials.
[0014] The present invention also provides a method for preparing the above-mentioned MnO2-Au composite nanomaterial, comprising the following steps:
[0015] Manganese dioxide nanomaterial, sodium citrate, polyvinylpyrrolidone, water and chloroauric acid are mixed and heated to boiling to obtain the MnO2-Au composite nanomaterial.
[0016] Preferably, the mass ratio of the manganese dioxide nanomaterial to chloroauric acid is (10-20):1; more preferably (10-15):1; further preferably 12.5:1.
[0017] Preferably, the mass ratio of the sodium citrate to chloroauric acid is 1:(0.1-1); more preferably 1:(0.1-0.5); further preferably 1:0.4.
[0018] Preferably, the mass ratio of polyvinylpyrrolidone to sodium citrate is 1:(0.04-0.08); more preferably 1:(0.04-0.06); further preferably 1:0.058.
[0019] In a specific embodiment of the present invention, the method for preparing the MnO2-Au composite nanomaterial comprises the following steps:
[0020] Manganese dioxide nanoparticles are dispersed in water, and then sodium citrate, chloroauric acid and polyvinylpyrrolidone are added, and heated to boiling to obtain the MnO2-Au composite nanomaterial.
[0021] The present invention also provides the use of the above-mentioned MnO2-Au composite nanomaterial or the MnO2-Au composite nanomaterial prepared by the above-mentioned preparation method in scavenging oxygen free radicals.
[0022] The MnO2-Au composite nanomaterial has a better effect of removing oxygen free radicals than the MnO2 nanomaterial.
[0023] The present invention also provides a hydrogel composite material, comprising polyethylene glycol hydrogel and the above-mentioned MnO2-Au composite nanomaterial loaded on the surface of the polyethylene glycol hydrogel;
[0024] The polyethylene glycol hydrogel comprises a product obtained by cross-linking and polymerization of four-arm polyethylene glycol active ester and four-arm polyethylene glycol amine.
[0025] The four-arm polyethylene glycol active esters described in the present invention are all 4-ARM-PEG-NHS.
[0026] The four-arm polyethylene glycol amines described in the present invention are all 4-ARM-PEG-NH2.
[0027] The hydrogel composite material continuously releases manganese ions within 14 days, indicating that the MnO2-Au composite nanomaterial can be effectively released from the hydrogel composite material to further scavenge oxygen free radicals.
[0028] Preferably, in the present invention, the loading amount of the MnO2-Au composite nanomaterial in the hydrogel composite material is 0.1 wt%-10wt%; more preferably 0.5 wt%-4wt%; further preferably 2wt%.
[0029] The present invention also provides a method for preparing the above-mentioned hydrogel composite material, comprising the following steps:
[0030] The hydrogel composite material is prepared by mixing and reacting MnO2-Au composite nanomaterial, four-arm polyethylene glycol active ester, four-arm polyethylene glycol amine and solvent;
[0031] The solvent is selected from phosphate buffer or water. The water is preferably ultrapure water.
[0032] In the above preparation method, the four-arm polyethylene glycol active ester and the four-arm polyethylene glycol amine undergo cross-linking polymerization to obtain the polyethylene glycol hydrogel of the present invention.
[0033] Preferably, in the present invention, the mass ratio of the MnO2-Au composite nanomaterial to the four-arm polyethylene glycol active ester is 1:(2-10); more preferably 1:4.
[0034] Preferably, the mass ratio of the four-arm polyethylene glycol active ester to the four-arm polyethylene glycol amine is 1:(1-5); more preferably 1:1.
[0035] The hydrogel composite material of the present invention has the advantages of less inflammatory cell infiltration and more complete wound epidermis layer than MnO2 gel material during wound healing treatment. The MnO2 gel material includes polyethylene glycol hydrogel and MnO2 nanomaterial loaded on the surface of polyethylene glycol hydrogel. The polyethylene glycol hydrogel includes a product obtained by cross-linking and polymerization of four-arm polyethylene glycol active ester and four-arm polyethylene glycol amine.
[0036] Compared with the above-mentioned MnO2 gel material, the MnO2-Au gel material described in the present invention can more effectively promote high-quality healing of skin tissue after reversing the high oxidative stress microenvironment.
[0037] The present invention also provides the use of the above hydrogel composite material or the hydrogel composite material prepared by the above preparation method in the preparation of a wound healing drug.
[0038] Compared with the prior art, the MnO2-Au composite nanomaterial provided by the present invention is composed of nano-flower-shaped manganese dioxide and spherical gold nanoparticles loaded on its surface; the Au loading in the MnO2-Au composite nanomaterial is 0.8wt%~1.2 wt%; the particle size of the spherical gold nanoparticles is 18~28 nm. The MnO2-Au composite nanomaterial has excellent continuous oxygen free radical scavenging ability, good stability and biocompatibility. The MnO2-Au composite nanomaterial can regulate the redox imbalance in the diabetic microenvironment, and has good application potential in diabetic wound healing and oral mucosal wound healing under chronic inflammatory conditions. The hydrogel composite material prepared by the method has a more excellent continuous oxygen free radical scavenging ability, can effectively inhibit cell oxidative stress damage, and thus significantly promote the healing of wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The size distribution diagram of Au NPs in the MnO2-Au nanomaterial prepared in Example 1;
[0040] Figure 2 Characterization diagrams of the MnO2-Au composite nanomaterial prepared in Example 1 and the MnO2 nanomaterial prepared in Comparative Example 1, wherein the morphology diagrams of the MnO2 nanomaterial and the MnO2-Au composite nanomaterial under scanning electron microscope are A and B, the result analysis diagrams of EDS energy spectrum are C and D, the transmission electron microscope diagrams are E and F, and the high-resolution transmission electron microscope diagrams are G and H;
[0041] Figure 3 The results of hydrogen peroxide cracking and cell active oxygen scavenging performance of the MnO2-Au composite nanomaterial of Example 2, the MnO2 nanomaterial of Comparative Example 1 and the control 1 group (PBS buffer containing 1 mM H2O2), wherein A is a diagram showing the effect of removing H2O2 within 48 hours, a is a bar graph showing the residual H2O2 content in the reaction system after 1 to 2 hours of reaction, and B is a schematic diagram of H2O2 cracking catalyzed by the MnO2-Au composite nanomaterial (EF: Fermi energy);
[0042] Figure 4 A is a schematic diagram of the preparation of in vitro simulated medium (SM) for HDF cell experiments, B is a cell viability diagram after HDF cells were treated with SM for 24 hours, C is a mean fluorescence intensity diagram of oxidative stress after HDF cells were treated with SM for 30 minutes, and D is a representative fluorescence diagram of oxidative stress, where NC is a negative control group of pure HDF cells (HDF cells are directly cultured in FM medium), and PC is a positive control group of cells treated with H2O2 (HDF cells are incubated in FM medium containing 500 μmol / L H2O2 at 37°C for 1 hour);
[0043] Figure 5 The HDF cell migration staining diagram (A), HDF cell migration cell counting results (B) and type I collagen gene expression diagram in HDF cells of control 2 group (HDF cell group incubated at 37°C for 1 hour in FM medium containing 500 μmol / L H2O2), MnO2 nanomaterials of comparative example 1, and MnO2-Au composite nanomaterials of example 2 are shown;
[0044] Figure 6The figures are characterization and performance test diagrams of the MnO2-Au gel material of Example 2, the MnO2 gel material of Comparative Example 2 and the simple gel material of Comparative Example 4, wherein AC are SEM images of the above materials, the black arrow in B points to the MnO2-Au nanomaterial, and the black arrow in C points to the MnO2 nanomaterial; DF are energy spectra of the above materials, respectively; G is a graph of the Mn ion concentration released by the above materials after 0-14 days; H is a graph of the hydrogen peroxide cleavage effect after the above materials and Blank 1 group (PBS buffer containing 1 mM H2O2) were treated for 2 hours;
[0045] Figure 7 The figures show the results of promoting skin wound healing in diabetic mice by the MnO2-Au gel material of Example 2, the MnO2 gel material of Comparative Example 2, the simple gel material of Comparative Example 4 and Blank 2 group (blank wound group without any material treatment), wherein A is a schematic diagram of the full-thickness injury model of mouse skin defect; B is the wound images and wound overlap images on days 0, 3, 7 and 14 after treatment of the above-mentioned groups (the scale is 5 mm); C is the wound healing ratio results within 14 days in the above-mentioned groups; D, E and F are DHE fluorescence staining images, H&E staining images and Masson staining images of the wound tissues on day 14 after treatment of the above-mentioned groups, respectively, wherein the dotted boxes are local enlarged images. DETAILED DESCRIPTION
[0046] In order to further illustrate the present invention, the MnO2-Au composite nanomaterial provided by the present invention, its preparation method and application, and the hydrogel composite material are described in detail below in conjunction with the embodiments.
[0047] Example 1
[0048] A method for preparing a manganese-based material capable of inhibiting oxidative stress at the nanoscale, the process is as follows:
[0049] (1) Preparation of MnO2 nanomaterials
[0050] Manganese dioxide nanoparticles were synthesized by hydrothermal reaction. 1.0 g KMnO4 and 0.4 g MnSO4 powder were continuously stirred and mixed in 30 ml deionized water. After mixing, they were transferred to a stainless steel autoclave lined with polytetrafluoroethylene. Then, they were heated and stirred at 140°C for 1 hour. Then, they were cooled to room temperature. Then, the obtained manganese dioxide nanomaterial was washed and dried. The obtained MnO2 nanomaterial had the morphology of nanoflowers (such as Figure 2 A).
[0051] (2) Preparation of MnO2-Au composite nanomaterials
[0052] The above 100 mg of MnO2 nanomaterials were added to 100 mL of deionized water and ultrasonically treated. Then 140 mg of PVP powder and 20 mg of sodium citrate were added and heated to boiling under continuous stirring. 200 mM / L of HAuCl4 (aq) was added to the reaction system and the mixture was boiled for 1 hour. Finally, the nanomaterials were washed and dried to obtain MnO2-Au composite nanomaterials, the morphology of which was monodispersed spherical Au NPs uniformly dispersed on the nanoflower-like MnO2 surface.
[0053] Depend on Figure 1 It can be seen that the Au particles modified on the surface of the manganese oxide material are uniform in size, with a diameter of about 22.81 nm.
[0054] Figure 2 Figures A and B show that both the MnO2 nanomaterials and the MnO2-Au composite nanomaterials have flower-like morphologies and similar particle sizes. The average size of MnO2 is about 580nm, and the average size of MnO2-Au is about 540nm. In addition, the Au nanoparticles (Au NPs) deposited on the surface of the MnO2-Au composite nanomaterials are monodispersed spherical morphologies with relatively uniform sizes ( Figure 2 F), uniformly dispersed on MnO2.
[0055] Figure 2 Figures C and D show that both the MnO2 nanomaterials and the MnO2-Au composite nanomaterials contain the elements K, Mn and O, and the MnO2-Au composite nanomaterials also contain the element Au.
[0056] Figure 2 Figures E, F, G and H show that the microstructures of MnO2 nanomaterials and MnO2-Au composite nanomaterials both present a typical nanosheet stacking structure.
[0057] Figure 3 Figures A and a show that the MnO2-Au composite nanomaterials of the present invention significantly promote the elimination of H2O2, and the rapid removal of oxygen free radicals is particularly significant within the initial 2 hours of the reaction. After 1 hour of reaction, the residual hydrogen peroxide rate of the MnO2-Au composite nanomaterial group is 40.03±0.60%, and after 2 hours, the residual hydrogen peroxide rate is 24.84±1.85%, while the residual rate of MnO2 material removal is 72.53±2.02% (1 hour) and 36.05±1.05% (2 hours), which indicates that the Au-modified nano MnO2 material exhibits higher catalytic cracking efficiency.
[0058] Figure 3Figure B shows that due to the different Fermi levels of MnO2 and Au nanoparticles, the introduction of Au nanoparticles makes MnO2 have more oxygen vacancies, thereby improving the catalytic performance of MnO2-Au composite nanomaterials. At the same time, the electronic regulation between MnO2 and Au improves the service life and long-term stability of MnO2-Au composite nanomaterials, and comprehensively improves the performance of catalytic cracking of hydrogen peroxide.
[0059] The H2O2-treated culture medium was selected to simulate the diabetic wound microenvironment. MnO2 material or MnO2- Au composite nanomaterial (1 mg / mL) was placed in a culture medium containing 500 μmol / L H2O2, incubated at 37°C for 1 hour, and then centrifuged to remove the nanoparticles. The remaining cell culture medium is called simulated medium (SM). This process is as follows Figure 4 As shown in Figure A.
[0060] Figure 4 Figure B shows that both MnO2 materials and MnO2-Au nanomaterials effectively alleviated the effects of oxidative stress damage (using conditioned medium SM stimulation as a model simulating in vivo environmental oxygen free radical stimulation) on the viability of HDF cells (human dermal fibroblasts), but the effect of MnO2-Au nanomaterials in protecting HDF cells from hydrogen peroxide damage was more obvious.
[0061] Figure 4 Figures C and D show that the average fluorescence intensity of oxidative stress after SM treatment of HDF cells for 30 minutes is the positive control group PC group>MnO2 nanomaterials>MnO2-Au composite nanomaterials (MnO2-Au composite nanomaterials are approximately equal to the negative control group NC), which indicates that the MnO2-Au nanomaterial group significantly reduces the fluorescence intensity inside and outside the HDF cells after reactive oxygen stimulation. In addition, as shown in Figure C, compared with the positive control group PC group (402.63±73.07%), the ROS (reactive oxygen) levels of HDF cells under hydrogen peroxide conditions pretreated with MnO2 and MnO2-Au were reduced to 229.70±32.72% and 109.96±33.92%, respectively, among which there was no statistically significant difference between the MnO2-Au group and the negative control group (100±3.81%), which indicates that the MnO2-Au nanomaterials described in the present invention can make the ROS level of HDF cells extremely low, close to the normal HDF cell state.
[0062] Figure 5Figure A shows that the proportion of HDF cell migration in MnO2 nanomaterials and MnO2-Au composite nanomaterials was significantly improved compared with the control 2 groups at 6 h and 24 h, and the HDF cell migration of MnO2-Au composite nanomaterials was greater than that of MnO2 nanomaterials. Figure B shows that H2O2 treatment inhibited the migration of HDF cells, while MnO2 nanomaterials and MnO2-Au composite nanomaterials effectively increased the number of HDF cell migration, and the MnO2-Au composite nanomaterial increased the number of HDF cell migration more within 6 hours, indicating that MnO2-Au composite nanomaterials can effectively alleviate the oxidative stress microenvironment, create an environment conducive to cell migration, and lay the foundation for subsequent skin tissue repair and regeneration.
[0063] Figure 5 Figure C shows that MnO2-Au composite nanomaterials can effectively restore the expression of COL-1A1 gene in HDF cells under oxidative stress stimulation.
[0064] Example 2
[0065] MnO2-Au gel material
[0066] A method for preparing a gel material that inhibits composite nanomaterials, the process is as follows:
[0067] (1) Preparation of MnO2 nanomaterials
[0068] Manganese dioxide nanoparticles were synthesized by hydrothermal reaction. 1.0 g KMnO4 and 0.4 g MnSO4 powder were continuously stirred and mixed in 30 ml deionized water. After mixing, they were transferred to a stainless steel autoclave lined with polytetrafluoroethylene. Then, they were heated and stirred at 140°C for 1 hour. Then, they were cooled to room temperature. Then, the obtained MnO2 nanomaterials were washed and dried.
[0069] (2) Preparation of MnO2-Au composite nanomaterials
[0070] 100 mg of MnO2 nanomaterials were added to 100 mL of deionized water and ultrasonically treated. Then 140 mg of PVP powder and 20 mg of sodium citrate were added and heated to boiling under continuous stirring. 200 mM / L of HAuCl4(aq) was added to the reaction system and the mixture was boiled for 1 hour. Finally, the obtained nanomaterials were washed and dried to obtain MnO2-Au composite nanomaterials.
[0071] (3) Preparation of MnO2-Au gel material
[0072] The prepared MnO2-Au composite nanomaterial was dissolved in a PBS solution at a concentration of 1 mg / mL. Four-arm polyethylene glycol active ester (4-ARM-PEG-NHS, molecular weight 10kD) and four-arm polyethylene glycol amine (4-ARM-PEG-NH2, molecular weight 10kD) were blended in a molar ratio of 1:1 and added to the PBS solution containing the MnO2-Au composite nanomaterial. The solid powder concentrations of 4-ARM-PEG-NHS and 4-ARM-PEG-NH2 were both 4% (w / v). The two solutions were blended by a dual-phase injector to prepare the MnO2-Au gel material.
[0073] Comparative Example 1
[0074] The preparation method of MnO2 nanomaterials is as follows:
[0075] Manganese dioxide nanoparticles were synthesized by hydrothermal reaction. 1.0 g KMnO4 and 0.4 g MnSO4 powder were continuously stirred and mixed in 30 ml deionized water. After mixing, they were transferred to a stainless steel autoclave lined with polytetrafluoroethylene. Then, they were heated and stirred at 140°C for 1 hour. Then, they were cooled to room temperature. Then, the nanomaterials were washed and dried to obtain MnO2 nanomaterials.
[0076] Comparative Example 2
[0077] Preparation of MnO2 gel material
[0078] A method for preparing a gel material that inhibits composite nanomaterials, the process is as follows:
[0079] (1) Manganese dioxide nanoparticles were synthesized by hydrothermal reaction. 1.0 g KMnO4 and 0.4 g MnSO4 powder were continuously stirred and mixed in 30 ml deionized water. After mixing, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene. The mixture was then heated and stirred at 140°C for 1 hour. The mixture was then cooled to room temperature. The obtained MnO2 nanomaterial was then washed and dried.
[0080] (2) The prepared MnO2 nanomaterial was dissolved in a PBS solution at a concentration of 1 mg / ml. Four-arm polyethylene glycol active ester (4-ARM-PEG-NHS, molecular weight 10kD) and four-arm polyethylene glycol amine (4-ARM-PEG-NH2, molecular weight 10kD) were mixed in a molar ratio of 1:1 and added to the above PBS solution. The solid powder concentrations of 4-ARM-PEG-NHS and 4-ARM-PEG-NH2 were both 4% (w / v). The two solutions were blended by a biphasic injector to prepare a MnO2 gel material.
[0081] Comparative Example 3
[0082] Blank FM medium
[0083] HDF cells incubated with pure FM culture medium (Cat. No. 2301, ScienCell, USA) and hydrogen peroxide mixed solution were used as the comparison of nanomaterials, namely the negative control group NC group of pure HDF cells (HDF cells directly cultured with FM culture medium).
[0084] Comparative Example 4
[0085] Simple gel material
[0086] Four-arm polyethylene glycol active ester (4-ARM-PEG-NHS, molecular weight 10kD) and four-arm polyethylene glycol amine (4-ARM-PEG-NH2, molecular weight 10kD) were mixed in a molar ratio of 1:1 and added to a PBS solution. The solid powder concentrations of 4-ARM-PEG-NHS and 4-ARM-PEG-NH2 were both 4% (w / v). The two solutions were blended using a biphasic injector to prepare a simple gel material.
[0087] Figure 6 The AF images show that the MnO2 nanomaterials and the MnO2-Au composite nanomaterials are uniformly dispersed on the surface of the hydrogel.
[0088] Figure 6 The G graph shows that the MnO2 nanomaterial and the MnO2-Au composite nanomaterial release the Mn element from the hydrogel over time, indicating that the MnO2-Au composite nanomaterial can be effectively released from the hydrogel, laying the foundation for the subsequent oxygen free radical scavenging.
[0089] Figure 6 The H diagram shows that the single gel material Gel group prepared in Comparative Example 4 does not have effective peroxide scavenging ability, and the peroxide catalytic scavenging ability of the MnO2-Au gel material depends on the MnO2-Au composite nanomaterial.
[0090] Figure 7 Figures B and C show that on the 14th day after surgery, the wound healing degree of each group was different, and the MnO2-Au gel group showed the fastest wound healing speed. The wound area on the 14th day after surgery was significantly different from that of the other groups, which shows the correlation between impaired wound healing and oxidative stress stimulation.
[0091] Figure 7Figure E shows that the H&E staining results show that scattered inflammatory cell infiltration and scab tissue necrosis can be seen in the epidermis of Blank 2 group (blank wound group without any material treatment) and Gel alone group of Comparative Example 4. In contrast, the inflammatory cell infiltration of the MnO2 gel material group and the MnO2-Au gel material group was very small, and the epidermis was intact, and the inflammatory cell infiltration of the MnO2-Au gel material group was even less, and the epidermis was more intact.
[0092] Figure 7 Figure F shows that although striped keratin-positive layers were found in all groups, the collagen deposition under MnO2-Au gel material treatment was richer, more extensive and more orderly, indicating that MnO2-Au gel material can more effectively promote high-quality healing of skin tissue after reversing the high oxidative stress microenvironment.
[0093] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A MnO 2 -Au composite nanomaterials, It is characterized in that It is composed of nanoflower-shaped manganese dioxide and spherical gold nanoparticles loaded on its surface; The MnO 2 -The Au loading in the Au composite nanomaterial is 0.8 wt%~1.2 wt%; The particle size of the spherical gold nanoparticles is 18-28 nm.
2. MnO according to claim 1 2 -Au composite nanomaterials, It is characterized in that The MnO 2 -The particle size of Au composite nanomaterials is 470~630 nm.
3. MnO according to claim 1 2 -Au composite nanomaterial preparation method, It is characterized in that The following steps are involved: Manganese dioxide nanomaterial, sodium citrate, polyvinylpyrrolidone, water and chloroauric acid are mixed and heated to boiling to obtain the MnO 2 -Au composite nanomaterials.
4. The preparation method according to claim 3, It is characterized in that The mass ratio of the manganese dioxide nanomaterial to chloroauric acid is (10-20):1; The mass ratio of sodium citrate to chloroauric acid is 1:(0.1~1); The mass ratio of the polyvinylpyrrolidone to sodium citrate is 1:(0.04-0.08).
5. MnO according to claim 1 or 2 2 -Au composite nanomaterial or MnO prepared by the preparation method according to claim 3 or 4 2 -Application of Au composite nanomaterials in scavenging oxygen free radicals.
6. A hydrogel composite material, It is characterized in that The method comprises a polyethylene glycol hydrogel and the MnO2 as claimed in claim 1 loaded on the surface of the polyethylene glycol hydrogel. 2 -Au composite nanomaterials; The polyethylene glycol hydrogel comprises a product obtained by cross-linking and polymerization of four-arm polyethylene glycol active ester and four-arm polyethylene glycol amine.
7. The hydrogel composite material according to claim 6, It is characterized in that The MnO in the hydrogel composite material 2 -Au composite nanomaterial loading is 0.1 wt%~10 wt%.
8. The method for preparing the hydrogel composite material according to claim 6, It is characterized in that The following steps are involved: MnO 2 -Au composite nanomaterials, four-arm polyethylene glycol active ester, four-arm polyethylene glycol amine and solvent are mixed to prepare the hydrogel composite material; The solvent is selected from phosphate buffer or water.
9. The preparation method according to claim 8, It is characterized in that The MnO 2 -The mass ratio of Au composite nanomaterials and four-arm polyethylene glycol active ester is 1:(2~10); The mass ratio of the four-arm polyethylene glycol active ester to the four-arm polyethylene glycol amine is 1:(1-5).
10. Use of the hydrogel composite material according to claim 6 or 7 or the hydrogel composite material prepared by the preparation method according to claim 8 or 9 in preparing a drug for treating wound healing.
